Prime and target immunization protects against liver-stage malaria in mice - Gola, A; Silman, D; Walters, A; Uderhardt, S; Salman, A; Halbroth, B; Bellamy, D; Bowyer, G; Powlson, J; Baker, M; Venkatraman, N; Poulton, I; et al. (American Association for the Advancement of Science, 2018)
Despite recent advances in treatment and vector control, malaria is still a leading cause of death, emphasizing the need for an effective vaccine. The malaria life-cycle can be sub divided into three stages: the invasion and growth within liver hepatocytes (pre-erythrocytic stage), the blood- (erythrocytic stage) and finally the sexual-stage (occurring within the mosquito vector). Antigen-specific CD8+ T-cells are effectively induced by heterologous prime-boost viral vector immunization and known to correlate with liver stage protection. However, liver-stage malaria vaccines have struggled to generate and maintain the high numbers of Plasmodium-specific circulating T-cells necessary to confer sterile protection. Here, we describe an alternative “prime and target” vaccination strategy aimed specifically at inducing high numbers of tissue-resident memory T-cells present in the liver at the time of hepatic infection. This approach bypasses the need for very high numbers of circulating T-cells and markedly increases the efficacy of subunit immunization against liver-stage malaria using clinically relevant antigens and clinically tested viral vectors in murine challenge models. Translation to clinical use has begun, with encouraging results from a pilot safety and feasibility trial of intravenous chimpanzee adenovirus vaccination in humans. This work highlights the value of a prime-target approach for immunization against malaria and suggests that this strategy may represent a more general approach for prophylaxis or immunotherapy of other liver infections and diseases.